2018
DOI: 10.21037/hbsn.2017.08.02
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of preoperative CT liver volumetry in living donor hepatectomy and its clinical implications

Abstract: CT volumetry overestimate LL graft and underestimate LLS graft weight. This should be factored in when selecting LL graft by taking higher GRWR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
1
23
1
Order By: Relevance
“…In this study, we obtained a statistically signicant strong correlation between EGW and AGW for RL grafts with MHV (Spearman's correlation r =0.786 and p < 0.001), RL grafts without MHV (Spearman's correlation r =0.968 and p < 0.001) and LL grafts (Spearman's correlation r =0.809 and p < 0.001). This is consistent with a study conducted by Sanjay Goja et al in 842 donors, in which they found a statistically signicant strong correlation between EGW and AGW for RL grafts (r=0.82, P<0.001) and LL grafts (r=0.81, P<0.001) and statistically signicant moderate correlation between EGW and AGW for LLS grafts (r=0.49, P<0.001) (7). A study by T. Yoneyama et al also showed that the correlation coefcient between EGW and AGW was 0.84 in right lobe grafts and 0.85 in left lobe grafts (p<0.001), indicating a statistically signicant correlation which is consistent with our results (8).…”
supporting
confidence: 92%
“…In this study, we obtained a statistically signicant strong correlation between EGW and AGW for RL grafts with MHV (Spearman's correlation r =0.786 and p < 0.001), RL grafts without MHV (Spearman's correlation r =0.968 and p < 0.001) and LL grafts (Spearman's correlation r =0.809 and p < 0.001). This is consistent with a study conducted by Sanjay Goja et al in 842 donors, in which they found a statistically signicant strong correlation between EGW and AGW for RL grafts (r=0.82, P<0.001) and LL grafts (r=0.81, P<0.001) and statistically signicant moderate correlation between EGW and AGW for LLS grafts (r=0.49, P<0.001) (7). A study by T. Yoneyama et al also showed that the correlation coefcient between EGW and AGW was 0.84 in right lobe grafts and 0.85 in left lobe grafts (p<0.001), indicating a statistically signicant correlation which is consistent with our results (8).…”
supporting
confidence: 92%
“…For the Left lateral segment (LLS) graft, CT may underestimate the volume because the actual surgical plane of transection is around 1 cm to the right of a falciform ligament whereas radiological plane is at falciform ligament. In addition to that non-hepatic tissues like falciform ligament which are excluded in CT volumetry are a part of LLS allograft included in AGW [14].…”
Section: Discussionmentioning
confidence: 99%
“…A GRWR of 0.8% was desirable, but a GRWR as low as 0.60% was accepted in patients with MELD scores of 18 or less and Karnofsky Performance Status (KPS) scores of >60. The minimum acceptable future liver remnant was 30% of the total liver volume estimated on computed tomography scan prior to transplant . The actual graft weight was measured on the bench after flushing the graft with University of Wisconsin solution at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The minimum acceptable future liver remnant was 30% of the total liver volume estimated on computed tomography scan prior to transplant. (21) The actual graft weight was measured on the bench after flushing the graft with University of Wisconsin solution at 4°C. The actual GRWR was considered while deciding the method of PIM.…”
Section: Standard Ldlt Protocolmentioning
confidence: 99%